2002
DOI: 10.1159/000066456
|View full text |Cite
|
Sign up to set email alerts
|

Change in Generic and Disease-Specific Health-Related Quality of Life during a One-Year Period in Patients with Newly Detected Chronic Obstructive Pulmonary Disease

Abstract: Background: Although the health-related quality of life (HRQoL) in patients with chronic obstructive pulmonary disease (COPD) has been assessed by generic or disease-specific HRQoL measures, the responsiveness of the generic HRQoL measures is generally weak. Objectives: To investigate the responses generated by generic and disease-specific HRQoL questionnaires, we prospectively followed the clinical course of patients with newly detected COPD after the initiation of treatment. Methods: A prospective, longitudi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 23 publications
1
12
0
1
Order By: Relevance
“…This finding is compatible with previous results reported for patients with COPD (27). However, scores on the NHP commonly exhibit such end effects (28).…”
Section: Discussionsupporting
confidence: 93%
“…This finding is compatible with previous results reported for patients with COPD (27). However, scores on the NHP commonly exhibit such end effects (28).…”
Section: Discussionsupporting
confidence: 93%
“…Disease-specific questionnaires like the St George's Respiratory Questionnaire (SGRQ) reflect a wide range of different health impacts in COPD [1], are designed to provide an overall measure of impairment, and are now used widely in randomized controlled trials in COPD. A number of relatively small longitudinal observational studies [2-5] have shown that a decline in health status may be seen over time, but there have been relatively few studies of long-term treatment effects on health status decline. The first of these was the Inhaled Steroids in Obstructive Lung Disease (ISOLDE) study, which showed that health status measured using the SGRQ deteriorated progressively over 3 years [6], an effect that was slowed by the inhaled corticosteroid (ICS) fluticasone propionate (FP) [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…But operationalizing HRQoL poses several methodologic difficulties [7,8]. In addition to the problems of reliability and validity that are inherent in selfreport questionnaires, there is no consensus among researchers on whether HRQoL should be measured by generic or disease-specific approaches [7,9,10]. On the one hand, disease-specific HRQoL questionnaires offer the advantage of generally higher responsiveness [10].…”
Section: Introductionmentioning
confidence: 99%